PATIENT KNOWLEDGE AS DETERMINANT OF MEDICATION ADHERENCE IN TYPE 2 DIABETES MELLITUS AT SIMARMATA PRIMARY HEALTH CENTER, SAMOSIR REGENCY - Laura Mariati Siregar; Nurpina Simarmata; Vierto Irennius Girsang; Asima Sirait (Jurnal Ilmiah Keperawatan, 2026)
Background: Diabetes mellitus management includes dietary restrictions, increased physical activity, an appropriate medication regimen, regular medical follow-up, and periodic metabolic monitoring through laboratory examinations. Adherence of diabetes mellitus patients to therapy that has been indicated and prescribed by physicians will lead to positive therapeutic effects. Purpose: The aim of this study is to identify the relationship between patient knowledge and medication adherence among type 2 diabetes mellitus patients at Simarmata Primary Health Center, Samosir Regency. Methods: This study employed a quantitative research approach with a cross-sectional design. The population consisted of all diabetes mellitus patients who were undergoing routine medical follow-up at the health center, totaling 32 individuals. The sample was selected using a total sampling technique, resulting in 32 respondents. Results: The study findings showed that 56.3% of respondents had good knowledge, with 34.4% demonstrating adherence to medication and 21.9% non-adherence. Respondents with moderate knowledge accounted for 37.5%, of whom 34.4% were non-adherent and only 3.1% adherent. The statistical test resulted in a significance value of Sig. = 0.001, which was lower than 0.005, indicating a significant relationship between knowledge and medication adherence. Conclusion: It can therefore be concluded that there is a significant relationship between patient knowledge and medication adherence among people with type 2 diabetes mellitus. Respondents are encouraged to further improve their adherence to prescribed medication in order to increase the likelihood of successful treatment outcomes and achieve a higher rate of recovery.